Effects of bed rest reduction after coronary angiography on local vascular complications and back pain - Ashktorab, T; Neishaboory, M; Piranfar, M; Alavi- Majd, H (Advances in Nursing & Midwifery, 2009)
Background Coronary heart diseases are increasing and one of the gold standards for diagnosis is catheterization. This method is associated with vascular complications such as bleeding, hematoma and arterial thrombosis. To prevent these complications, patients are restricted to bed for 6 hours after the procedure. This practice has been associated with back pain. Purpose This clinical trial was conducted to determine the effects of bed rest reduction after angiography on vascular complications and back pain of patients at Taleghani hospital in 2007. Methods 130 patients were selected by convenience sampling and randomly divided into two equal control and experimental groups. Bed rest durations were 6 and 4 hours in the control and experimental groups respectively. A checklist was used for vascular complications as well as hemodynamic status and the numeric pain intensity scale was applied for data collection. Results None of the patients in both groups developed vascular complications or hemodynamic alterations. However, the intensity of back pain was significantly lower in the experimental group (P<0/001). Conclusion Reducing the time of bed rest after cardiac angiography holds no risk and is possible. This involves no further vascular complication while increasing relaxation and reducing back pain in these patients. Keywords: Coronary angiography, Bed rest, Complications, Back pain.